Penggunaan Klausa Eksonerasi dalam Perjanjian Kerja antara Pekerja dengan Pengusaha di Indonesia - Nugroho, Handika Faqih (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
An exoneration clause is a clause whose contents are more in favor of a party with a higher position in casu a work agreement whose position is more dominant or higher is the employer, so that this exoneration clause can cause harm to workers whose position is below the employer, even though the agreement recognizes the principle of freedom of contract , but there is nothing that explicitly limits the use of exoneration clauses in work agreements. In answering these problems, this paper uses a normative method by collecting data from literature studies in the form of labor law regulations in Indonesia, doctrines, and court decisions. The results of this study are that work agreements may use exoneration clauses with limitations that do not differ from Article 1320 KUHPER jo. Article 52 of the Labor Law and the legal protection of workers who are harmed by the exoneration clause in the work agreement can carry out bipartite or conciliation to make an addendum/amendment to the work agreement or workers can cancel it in court if the work agreement contained in the exoneration clause differs from the terms of the validity of the work agreement.